Feasibility Of White Copra Business from Quality and Income Perspective at The Farmers Level - Suryadi, Suryadi; Apriyanto, Mulono; Ariyanto, Anto (Jurnal Mamangan, 2024)
This study aims to determine the feasibility of white copra business according to the perspective of quality and farmer income using SWOT analysis of White Copra Business. The selected research according to the research criteria using Accidental Sampling. Data collection techniques are observation, interviews, documentation studies. The analysis used is qualitative descriptive data analysis. Based on the results of the study, the resource aspect is adequate, the technical & technological aspects are relatively easy and cheap, the production aspect can produce continuously, the market & marketing aspect has many markets, while the BEP Grade A results are 88 Kg Grade B 113 Kg and Grade C 807 Kg, the financial aspect of the calculation results of the NPV Feasible Rp 1,093,785,500> 0, IRR Acceptable IRR results> 12%pa, BC ratio can be profitable because the results are 1.16%> 0.85%, PP period of 13 years 7 months annual capital return. Legal aspects of registered permits, and social & cultural aspects are environmentally friendly and new job vacancies. Meanwhile, for Strengths, the district with the largest land area (Strength), Weaknesses in the financial aspect (Weakness), Opportunities for opening vacancies new jobs (Opportunities) and Threats to unregistered permits (Treath).